Monotherapy with minocycline or trimethoprim/sulfamethoxazole for treatment of Stenotrophomonas maltophilia infections. (21st January 2016) - Hand, Elizabeth; Davis, Hannah; Kim, Ted; Duhon, Bryson
Abstract : Objectives: Stenotrophomonas maltophilia is a Gram-negative bacillus intermittently isolated from hospitalized patients. Trimethoprim/sulfamethoxazole is considered the treatment of choice for S. maltophilia infections, though limited by toxicities. Minocycline is utilized at our institution for S. maltophilia infections due to its improved tolerability and in vitro susceptibility rates. Our objective was to evaluate the effectiveness of minocycline monotherapy compared with trimethoprim/sulfamethoxazole monotherapy for treatment of S. maltophilia infections. Methods: Patients were identified via microbiology laboratory data and those with at least one positive culture for S. maltophilia were cross-referenced with pharmacy data to detect patients who received trimethoprim/sulfamethoxazole or minocycline. Patients initially receiving combination therapy were excluded. Our primary outcome was treatment failure, defined as receipt of alternative antibiotics with in vitro activity against S. maltophilia, isolation of S. maltophilia on repeat culture or death within 30 days of treatment. Results: Forty-five patients were evaluated. Overall mortality rate was 9% and equal between groups; 41% of patients (9/22) who received trimethoprim/sulfamethoxazole and 30% (7/23) of patients who received minocycline experienced treatment failure ( P  = 0.67). Patients who received minocycline were more likely to have had a recent acute kidney injury (AKI) (43.5% versus 9%; P  = 0.017) or chronic lung disease (52% versus 9%; P  = 0.003). Logistic regression showed consistent results of non-inferiority of the primary outcome when controlling for rates of underlying lung pathology and recent AKI ( P  = 0.728). Conclusions: Treatment failure did not differ between patients receiving trimethoprim/sulfamethoxazole or minocycline monotherapy for treatment of S. maltophilia infections.